Answer: x=-3, y=2
Step-by-step explanation: to solve using substitution, we need either x or y by itself in one equation. let's use x from the 2nd equation since it doesn't have a constant.
so the first equation stays the same at 2x+3y=0
for the second equation, rearrange to solve for x by moving the 2y to the right -> x=2y-1
then, we can plug in this x value to x in the first equation to get,
2(2y-1)+3y=0
then solve for y,
4y-2+3y=0
4y-3y=2
y=2
then to solve for x, plug in y in either of the initial equations. lets choose the second one.
so you'd have,
x+2(2)=1
x+4=1
x=-3